9(x-2)+6(x-3)=0

Simple and best practice solution for 9(x-2)+6(x-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x-2)+6(x-3)=0 equation:


Simplifying
9(x + -2) + 6(x + -3) = 0

Reorder the terms:
9(-2 + x) + 6(x + -3) = 0
(-2 * 9 + x * 9) + 6(x + -3) = 0
(-18 + 9x) + 6(x + -3) = 0

Reorder the terms:
-18 + 9x + 6(-3 + x) = 0
-18 + 9x + (-3 * 6 + x * 6) = 0
-18 + 9x + (-18 + 6x) = 0

Reorder the terms:
-18 + -18 + 9x + 6x = 0

Combine like terms: -18 + -18 = -36
-36 + 9x + 6x = 0

Combine like terms: 9x + 6x = 15x
-36 + 15x = 0

Solving
-36 + 15x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '36' to each side of the equation.
-36 + 36 + 15x = 0 + 36

Combine like terms: -36 + 36 = 0
0 + 15x = 0 + 36
15x = 0 + 36

Combine like terms: 0 + 36 = 36
15x = 36

Divide each side by '15'.
x = 2.4

Simplifying
x = 2.4

See similar equations:

| 5x+10y=5750 | | 5x(3x+2y)= | | 6(2x-5)-5x=2x-7+2 | | -9x+2x= | | 3(4x-2)=-42 | | -2x+3(-x+4)=0 | | 4(-2x-3)=-44 | | -9x+2x-7= | | -4(-2+3n)=44 | | y=2x^2-4x-6 | | 3(3x-3)=-45 | | 8(x+2)+4=0 | | x^2-20+100=0 | | 3(4b+2)=42 | | 12-7x=72-42x | | -5x+2(x+3)=-16 | | -3(4n+3)=-45 | | x^2+3xy*4x-12y= | | 4(3-4b)=-52 | | 40=3u-17 | | 4x+1+6=0 | | 3(4+3b)=48 | | 15b-6=-b-12 | | 34+2x+144=-6 | | 4(3-3k)=48 | | 3p(5p-2)= | | -3(4m-3)=45 | | 12-3z=3 | | -3(3+3x)=-45 | | m(7-x)=3-y | | 3-ln(1+2*x^2)=0 | | 2(x+2-3+4x)=2 |

Equations solver categories